2019
DOI: 10.1177/2292550319880919
|View full text |Cite
|
Sign up to set email alerts
|

Objective Comparison Between Spreader Grafts and Flaps for Mid-Nasal Vault Reconstruction: A Randomized Controlled Trial

Abstract: Objective: The goal of rhinoplasty is not exclusively aesthetic and the nasal function should always be considered. Several rhinoplasty techniques can participate in nasal valve dysfunction (eg, dorsal hump reductions). Therefore, mid-nasal vault reconstruction by spreader grafts or flaps is mandatory in these cases. To date, there is a literature gap in comparing both techniques objectively. This study shows an objective comparison between spreader grafts and flaps for mid-nasal vault reconstruction. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Inhalation FR on the left side and exhalation NAR on the right side were significantly reduced postoperatively in the SG group (p=0.025 and p=0.04, respectively). Finally, in the Ζeid et al study (25) , a statistically significant reduction in NAR, on the right and left sides, was observed six months postoperatively in both groups (SF and SG; p<0.001), with no significant difference between them.…”
Section: Rhinomanometrymentioning
confidence: 79%
See 4 more Smart Citations
“…Inhalation FR on the left side and exhalation NAR on the right side were significantly reduced postoperatively in the SG group (p=0.025 and p=0.04, respectively). Finally, in the Ζeid et al study (25) , a statistically significant reduction in NAR, on the right and left sides, was observed six months postoperatively in both groups (SF and SG; p<0.001), with no significant difference between them.…”
Section: Rhinomanometrymentioning
confidence: 79%
“…In four studies (19,20,24,25) , rhinomanometry was used. Görgülü et al (19) showed a significant decrease in both inhalation and exhalation nasal airway resistance (NAR; p<0.001) by using an active anterior rhinomanometry.…”
Section: Rhinomanometrymentioning
confidence: 99%
See 3 more Smart Citations